The implementation and evaluation of an athlete leadership development program with male youth ice hockey players - Boisvert, M. M.; Loughead, T. M.; Munroe-Chandler, K. J. (Frontiers in Psychology, 2022)
The purpose of the current study was to implement and evaluate an athlete leadership development program in youth boys ice hockey. The sample consisted of 14 male U17 hockey players (M = 16.46, SD = 0.78) from one team playing in a competitive hockey league. The players participated in six leadership intervention workshops over the course of the season, and completed inventories measuring athlete leadership behaviours, cohesion, and collective efficacy pre-and post-intervention. In addition, a focus group was conducted to assess the impact of the athlete leadership development program at the end of the season. Bayesian t tests showed that the leadership program generally helped to maintain levels of athlete leadership behaviours, cohesion, and collective efficacy pre-and post-intervention. The results of the focus group following the intervention revealed the players believed the leadership development program helped buffer against the negative effects of their on-ice performances.